Shape memory properties of highly textured Cu–Al–Ni–(Ti) alloys - Sobrero, Cesar Enrique (2012)
A strong alfa-fiber I texture with components from {0 0 1} 1 1 01 to {1 1 2}1 1 01 was developed in a polycrystalline Cu 13Al 5.5Ni 1Ti (wt%) shape memory alloy by hot extrusion at 800 ◦C (followed by recrystallization). Nearly fully recoverable strains up to the order of 6%, associated with cubic to monoclinic martensitic transformation beta1→ beta1, have been measured by thermal cycling under constant load experiments. Such a degree of strain recovery is typical of single crystals or polycrystalline arrays with a low degree of grain constraint, such as highly textured, bamboo like, extruded materials. The reversible transformation strains reached about 68% of the upper bound predicted by a Sachs-type model which averages the most favorable martensite variants in each grain, taking into account their orientation and disregarding interactions between them. Due to the strong texture introduced in the material, such high values of recoverable transformation strains are obtained even for specimens having a grain size/thickness ratio of ∼0.05, producing relatively high grain constraint.